PERANCANGAN SISTEM INFORMASI PENGGAJIAN KARYAWAN BERBASIS WEBSITE DI PERUSAHAAN X MENGGUNAKAN METODE PROTOTYPE - Deri Ramadiyan Hidayat; Dani Hamdani (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2024)
Company X is a growing company along with increasing customer demand and employee needs, which means a computerized system is needed to reduce errors in salary calculations. Currently the company is still less effective in calculating employee salaries because it still calculates, pays salaries and makes reports manually with methods in data collection, namely using interviews with company owners, conducting field observations and also questionnaires used for assessment of system design, the design method uses prototypes which have stages, namely listening to customers or collecting needs, Design and Test in assessment The trial uses a System Usability Scale (SUS) assessment of the respondent's assessment data, then calculates using the formula from the System Usability Scale, the smallest value is 78 and the largest value is 90 from the depalan respondent by answering 10 questions which has an average score of 86 from the qualifications in the table above "Very Feasible" the user interface must be designed so that it is easy to use and easy to understand so that payroll data input errors can be avoided. The use of autofill features and real-time data validation can help reduce input errors. And to create an effective user interface, it is necessary to understand user needs and expectations well. This can be achieved by involving users during the design and testing process, such as surveys, interviews, and prototype trials.